Living with HIV as Donor Aid Declines in Tanzania. Issue 3 (2nd April 2020) - Marten, Meredith G.
ABSTRACT: Fluctuations in global health funding can significantly impact the lives of people who depend on donor-funded programs for life-long care. In this article, I examine shifting HIV policies that expanded antiretroviral therapy (ART) while reducing "care" services meant to improve ART access and adherence. I describe how these changes were experienced by HIV+ women accessing ART at a hospital in Tanzania in 2011–2012, highlighting their increasing precarity and uncertainty for care amidst donor instability and eroding program services. This research suggests that stable funding in support of long-term care services is important to help HIV+ people maintain life-long ART. Abstract :